2004
DOI: 10.1111/j.1328-0867.2004.01884.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone‐associated biliary sludge and pseudocholelithiasis during childhood: A prospective study

Abstract: Reversible biliary sludge or pseudocholelithiasis due to ceftriaxone treatment is not a rare condition. Therefore it is benign, spontaneously resolved and clinical signs are usually absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 15 publications
(29 reference statements)
1
43
0
5
Order By: Relevance
“…The incidence of ceftriaxone-associated biliary sludge was reported between 17-57.5% (Schaad et al 1988;Papadopoulou et al 1999;Palanduz et al 2000;Herek et al 2001;Bor et al 2004;Ozturk et al 2005). Higher rates were reported with higher doses of ceftriaxone in those studies (100 mg/kg/day vs 60-70 mg/kg/day).…”
Section: Discussionmentioning
confidence: 82%
“…The incidence of ceftriaxone-associated biliary sludge was reported between 17-57.5% (Schaad et al 1988;Papadopoulou et al 1999;Palanduz et al 2000;Herek et al 2001;Bor et al 2004;Ozturk et al 2005). Higher rates were reported with higher doses of ceftriaxone in those studies (100 mg/kg/day vs 60-70 mg/kg/day).…”
Section: Discussionmentioning
confidence: 82%
“…The mixture of ceftriaxone and calcium ion is known to have the potential to cause incompatibility, resulting in biliary sludge and pseudocholelithiasis; even death has been reported. [12][13][14][15][16][17] In the case of ozagrel-calcium, the ionic product was less than 25% of the K sp . That is, the SI was <1, indicating that the solution was unsaturated, and the presence of ozagrel-calcium salts is unlikely.…”
Section: Comparison Of the Ozagrel Sodium Preparationsmentioning
confidence: 99%
“…It is therefore suggested that the ozagrel sodium preparation is compatible with calcium-containing products in vitro. 12) The risk of in vivo interactions between ozagrel and calcium can be calculated as follows: The maximum ozagrel concentration was reported to be 1139.82 ng/mL in human plasma at the end of an intravenous administration of 80 mg of ozagrel over a period of 2 h. 18 , which is 3.0×10 5 times lower than the K sp for ozagrel-calcium salt, when the calcium ion concentration in the plasma is 1.25 mmol/L. The halflife of ozagrel is short.…”
Section: Comparison Of the Ozagrel Sodium Preparationsmentioning
confidence: 99%
“…Bu yüzden "psödolitiyaz" olarak da adland›r›l-maktad›r (14)(15). Yap›lan çal›flmalarda seftriyakson tedavisi verilen çocuklarda yaklafl›k %25-30 oran›nda safra tafl› geliflti¤i ve tedavi kesildikten sonra k›sa sürede tafllar›n kendili¤inden kayboldu¤u bildirilmifltir (15)(16)(17). Çal›flmam›z-da hastalar›m›z›n 15'inde (%25) seftriyakson kullan›m› mevcuttu ve izlemde tafllar›n kayboldu¤u görülmüfltü.…”
unclassified